Hubungan Pengetahuan dengan Perilaku Perawat Ruang Rawawat Inap dalam Pencegahan Infeksi Nosokomial di Rumah Sakit PKU Muhammadiyah Sukoharjo - Lahar Bumi Mahardika; Triyanta Triyanta; Nabilatul Fanny (Journal of Educational Innovation and Public Health, 2024)
Nosocomial infections are a serious problem that often occurs in hospitals and can have a negative impact on patient safety. The role of nurses, especially in inpatient rooms, is very important in preventing these infections. Preliminary studies found 0.34% of HAIs in hospitals, 0.00% of urinary tract infections, 0.86% of Phlebitis, 0.00% of Ventilator Associated Pneumonia. The aim of this study was to determine the relationship between knowledge and behavior of nurses regarding the prevention of nosocomial infections.This type of research is quantitative research with a cross sectional approach. Data collection was carried out through questionnaires. This population is all nurses in the Inpatient Room at PKU Muhammadiyah Sukoharjo Hospital. The sample for this research was 42 respondents who were selected using the total data saturated sampling technique used, namely univariate and bivariate analysis (Spearman rho test).The results of the univariate analysis research showed that the nosocomial infection prevention process variable, nurse knowledge was in the good category at 100% and the nosocomial infection prevention process variable, nurse behavior was in the good category at 100%. The results of bivariate analysis using the Spearman's rho statistical test show that there is a p-value of 0.000, where this value is smaller than 0.05 with a coefficient value of 0.528. So it can be said that there is a relationship between knowledge and behavior of inpatient room nurses in preventing nosocomial infections at the PKU Muhammadiyah Sukoharjo hospital.In conclusion, there is a relationship between knowledge and behavior in preventing nosocomial infections at the PKU Muhammadiyah hospital. Suggestions: Increase counseling and training on preventing nosocomial infections for nurses and health workers and non-health workers at the PKU Muhammadiyah Sukoharjo Hospital.